Robust decision making for agile systems development Part 2: a decomposition and analysis - Barker, Stephen G.; Summers, Matthew P. (Elsevier, 2015)
The need for agility in operational systems within the defence enterprise and procurement domains has been identified by many authors, and over time, there have been a number of initiatives and programmes that have sought to identify the nature of agility, and the means by which it can be defined and employed within individual cases and scenarios. These have identified impediments to the successful realization of agile practices and methods, particularly the resilience of agile decision making throughout the conceptual understanding, design and implementation of the operational system. To further investigate the extent to which this process can be implemented in a robust and reliable manner, Cranfield University created the ‘Robust Enterprise-based Approach for Agility in Capability Through-life (REA2CT)’ framework, which provides a number of functional steps to institute a systems development lifecycle approach to producing agile solutions for use in networked systems and systems-of-systems. This paper builds upon the description of the framework[1] by applying the Axiomatic Design (AD) theory to identify where complexity exists within the requirements and design activities that underpin the framework. Using this analysis, this paper identifies ‘pain points’ within the REA2CT framework, and suggests necessary improvements to facilitate the implementation of agility throughout the systems development lifecycle.